Methotrexate and Lung Disease in Rheumatoid Arthritis: A Meta‐Analysis of Randomized Controlled Trials - Conway, Richard; Low, Candice; Coughlan, Robert J.; O'Donnell, Martin J.; Carey, John J. (Arthritis & rheumatology (Hoboken, N.J.), 2014)
Objective Methotrexate has shown efficacy for the treatment of several diseases, especially rheumatoid arthritis (RA). Methotrexate has also been implicated as a causative agent in interstitial lung disease. Patients with RA may develop pulmonary manifestations of their disease and are at increased risk of respiratory infection. The aim of this study was to evaluate the relative risk (RR) of pulmonary disease among patients with RA treated with methotrexate. Methods We searched the PubMed and Cochrane databases (publication dates January 1, 1990 to February 1, 2013) for double‐blind, randomized, controlled trials of methotrexate versus placebo or active comparator agents in adults with RA. Studies with <100 subjects or with a duration of <24 weeks were excluded. Two investigators independently searched both databases, and all of the investigators reviewed the selected studies. We compared differences in the RR using the Mantel‐Haenszel random‐effects method. Results A total of 22 studies with 8,584 participants met the inclusion criteria. Heterogeneity across studies was not significant (I2 = 3%), allowing combination of the trial results. Methotrexate was associated with an increased risk of all adverse respiratory events (RR 1.10, 95% confidence interval [95% CI] 1.02−1.19) and respiratory infection (RR 1.11, 95% CI 1.02−1.21). Patients treated with methotrexate were not at increased risk of death due to lung disease (RR 1.53, 95% CI 0.46−5.01) or noninfectious respiratory events (RR 1.02, 95% CI 0.65−1.60). A subgroup analysis of studies in which pneumonitis was described revealed an increased risk associated with methotrexate (RR 7.81, 95% CI 1.76−34.72). Conclusion Our study demonstrated a small but significant increase in the risk of lung disease in patients with RA treated with methotrexate compared with other disease‐modifying antirheumatic drugs and biologic agents.